Transmisi Keilmuan Kitab Fathul Qarib di Pesantren Yapink dan Attaqwa Bekasi - Rusli Hasbi; Nailil Huda; Fatihunnada Fatihunnada; Rizqa Ahmadi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
Fathul Qorib is the main reference for Islamic law studies in Indonesian Islamic boarding schools (Pesantren) because this book has a historical scientific heritage from the classical period of Islam. Indonesian Pesantrens have different characteristics in reading and learning Fathul Qorib based on conditions that develop and occur in the surrounding area. This paper uses the observation method by observing and interviewing students, ustadz/teachers, and kiai to trace patterns of knowledge transmission. The object of this research is Pesantren YAPINK and Attaqwa located in Bekasi district with two different types of Pesantren in terms of religious ideological background and the early history of the establishment of the Islamic boarding school. From the results of the research conducted, the reading of Fathul Qorib at the Pesantren YAPINK and Attaqwa has similarities and differences. The transmission of knowledge at YAPINK comes from internal and external sources because the teachers of the Fathul Qorib are graduated of YAPINK and other Pesantren such as Ploso Kediri and Sarang, while Attaqwa comes from internal-only because all Fathul Qorib teachers are from Attaqwa graduated.